KEVALIDAN DAN KEPRAKTISAN E-LKPD KIMIA DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH BERKONTEKS ISU-ISU SOSIAL SAINS - Nikmatur Rohmaya (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
The aim of this research is to describe and explain the validity and practicality of electronic student worksheets designed with a problem-based learning model and the context of social science issues. The data collection technique used is a questionnaire technique. The resulting data was analyzed using descriptive data analysis techniques. The validity tests carried out include validity tests in terms of material, media and language. The material validity test produced a value of 0.95 in the very valid category. The media validity test produced a value of 75.3 in the valid category. The language validity test produced a score of 96.13 in the very valid category. Practical tests are carried out by teachers and lecturers. The practicality test results by teachers and students were respectively 94.70 and 97.56 in the very practical category. Thus it can be concluded that the electronic student worksheets developed is valid and practical for use in learning.